Three-dimensional strut plate for the treatment of mandibular fractures: a systematic review - de Oliveira, J. C.S. [UNESP]; Moura, L. B. [UNESP]; de Menezes, J. D.S. [UNESP]; Gabrielli, M. A.C. [UNESP]; Pereira Filho, V. A. [UNESP]; Hochuli-Vieira, E. [UNESP] (Elsevier, 2018)
The treatment of mandibular fractures by open reduction and internal fixation is very variable. Thus, there are many controversies about the best fixation system in terms of stability, functional recovery, and postoperative complications. This systematic review sought scientific evidence regarding the best indication for the use of three-dimensional (3D) plates in the treatment of mandibular fractures. A systematic search of the PubMed/MEDLINE, Elsevier/Scopus, and Cochrane Library databases was conducted to include articles published up until November 2016. Following the application of the inclusion criteria, 25 scientific articles were selected for detailed analysis. These studies included a total of 1036 patients (mean age 29 years), with a higher prevalence of males. The anatomical location most involved was the mandibular angle. The success rate of 3D plates was high at this location compared to other methods of fixation. In conclusion, the use of 3D plates for the treatment of mandibular fractures is recommended, since they result in little or no displacement between bone fragments.
Keywords: 3D miniplate; grid plate; internal rigid fixation; mandible fracture; miniplate osteosynthesis; standard miniplate